Human issues of library and information work - Jela Steinerová (Information Research: An International Electronic Journal)
This paper examines philosophical, methodological and practical strategic aspects of library and information activity from the viewpoint of natural human and social factors. In contrast to traditional methodological patterns, real-life information problems and supportive methods of information seeking are stressed. The formulated conceptual framework is related to new competencies of information professionals, needs of information institutions and position of a human being in information processes. New methodological approach is outlined in models including factors with impact on a position of people in information work, human complexity and relationships of people and information. The resulting idea of human unity in information-related behaviour forms the vision of research directed to philosophy of a man in information science.